Haplotype diversity and association analysis of SNAC1 gene in wild rice germplasm - Singh, Bikram Pratap; Singh, Balwant; Kumar, Vinod; Singh, Pankaj Kumar; Jayaswal, Pawan K; Mishra, Shefali; Singh, Nagendra k (The Indian Journal of Genetics and Plant Breeding, 2016)
Effect of SNAC1 gene variants on drought tolerance was investigated in wild rice accessions. A total of 46 INDELs and 44 SNPs were identified including 17 SNPs in the coding region of the gene across the 164 Indian wild rice accessions and four cultivated rice genotypes. Based on the sequence variation, 25 haplotypes were identified including four specific to drought tolerant accessions. Translation of different allele sequences showed existence of five different SNAC1 protein variants. Evolutionary study on the basis of nucleotide sequence variation in the SNAC1 gene with different neutrality test suggested purifying selection in the wild rice accessions. Association analysis revealed that four SNPs were showing significant association with drought tolerance.The significantly associated SNPs and their associated haplotypes can further be used for the development of drought tolerant rice cultivars.